Desenvolvimento e caracterização do compósito biocerâmica/poli(E-caprolactona) com angiotensina 1-7 e avaliação em cultura primária de osteoblastos - Filipe Augusto de Faria Fonseca Macedo (2011)
Polycaprolactone (PCL) and biphasic ceramics (BCP) each have many applications as tissue repair materials. In this study, three-dimensional (3D) porous composite scaffolds of PCL: BCP (in 3:1 and 1:1 weight ratios) were fabricated using solvent casting and particulate leaching method with or without Angiotensin-(1-7). PCL:BCP scaffolds with high porosity and interconnected 3D pores were obtained and were analyzed using micro-computed tomography (micro-CT). The biocompatibilities of PCL:BCP with or without Ang-(1-7) were investigated during 3 and 7 days using MTT test and Alkaline Phosphatase Activity. Significant differences of all variables were tested by multivariate analysis (p<0.05). The results showed a structure with more finely distribution within the sample when the PCLBCP weight ratios were increased. The connectivity of pores was measured between fragmentation index (FI), and we noted that both analyzed samples present disconnected structures, with close values of FI. The higher is PCLBCP weight ratios leads to higher fractal dimension (FD). The in vitro tests using MTT showed that the constructs with and without Ang-(1-7) showed mild and moderate cytotoxic effects respectively. The Alkaline Phosphatase Activity showed no differences on the constructs with 3 days and only has decreasing activity on the constructs containing Ang-(1-7) on the 7 day. Thus, using solvent casting and particule leaching method we obtained 3D porous composites which have suitable shapes for bone defects having potential for drug delivery system and can be used in future in vivo tests.